The Abcc6a Knockout Zebrafish Model as a Novel Tool for Drug Screening for Pseudoxanthoma Elasticum - Van Gils, M.; Willaert, A.; Coucke, P. J.; Vanakker, O. M. (Frontiers in Pharmacology, 2022)
Pseudoxanthoma elasticum (PXE) is a multisystem ectopic mineralization disorder caused by pathogenic variants in the ABCC6 gene. Though complications of the disease can be treated, PXE itself remains currently intractable. A strategy for rapid and cost-effective discovery of therapeutic drugs would be to perform chemical compound screening using zebrafish, but this approach remains to be validated for PXE. In this paper, we validate a stable CRISPR/Cas9 abcc6a knockout zebrafish model–which has spinal column hypermineralization as its primary phenotypic feature–as a model system for compound screening in ectopic mineralization. We evaluated the anti-mineralization potential of five compounds, which had (anecdotal) positive effects reported in Abcc6 knockout mice and/or PXE patients. Abcc6a knockout zebrafish larvae were treated from 3 to 10 days post-fertilization with vitamin K1, sodium thiosulfate, etidronate, alendronate or magnesium citrate and compared to matching controls. Following alizarin red S staining, alterations in notochord sheath mineralization were semiquantified and found to largely congrue with the originally reported outcomes. Our results demonstrate that the use of this abcc6a knockout zebrafish model is a validated and promising strategy for drug discovery against ectopic mineralization.